The reverse mortgage market in New Zealand: key drivers of loan determination - Hutchison N; MacGregor B; Ngo T; Squires G; Webber DJ (Taylor and Francis Group, 2024)
This paper examines the drivers of loan principals in the reverse mortgage and equity release market in New Zealand using a hedonic price model (HPM) approach. Our analysis using reverse mortgages data between 2004–2021, sourced from one major reverse mortgage bank, provides four key findings. First, the term of payment for repaid reverse mortgages is positively associated with loan principals, implying that longer repayment terms allow applicants who were able to repay mortgages to borrow more. Second, there is partial evidence to suggest the presence of a positive linear impact of the value of the current property on its loan principal, in line with previous house price modelling studies. Third, older applicants (age 75+) borrow less than younger applicants, which may be due to their repaying ability. Fourth, we confirm a positive effect of interest rates on reverse mortgage amounts but reject the positive association between wider loan-to-value policy restrictions and equity release lending amounts. The results broadly highlight that the house price is more relevant than any individual characteristic of a property in determining loan principals, and that all drivers are relevant in the early stage of the development of the reverse mortgages market in New Zealand.
Keywords: Reverse mortgages; equity release; ageing population; housing finance